2019
DOI: 10.1503/jpn.180195
|View full text |Cite
|
Sign up to set email alerts
|

Altered reward-related effective connectivity in obsessive-compulsive disorder: an fMRI study

Abstract: Background: Obsessive-compulsive disorder (OCD) is characterized by anxiety-provoking, obsessive thoughts. Patients usually react to these thoughts with repetitive behaviours that reduce anxiety and are perceived as rewarding. Hence, reward plays a major role in the psychopathology of OCD. Previous studies showed altered activation in frontostriatal networks, among others, in association with the processing of reward in patients with OCD. Potential alterations in connectivity within these networks have, howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…3) FC-OC: We found 27 papers [17], [24], [36], [48], [58][59][60], [66], [70], [78], [87], [95], [97][98], [100][101], [119][120][121][122][123][124][125][126][127][128][129] involved in this connectivity category, spanning eight different task types, of which disease diagnosis had the highest prevalence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3) FC-OC: We found 27 papers [17], [24], [36], [48], [58][59][60], [66], [70], [78], [87], [95], [97][98], [100][101], [119][120][121][122][123][124][125][126][127][128][129] involved in this connectivity category, spanning eight different task types, of which disease diagnosis had the highest prevalence.…”
Section: Resultsmentioning
confidence: 99%
“…11) FC-INS: Nine papers, [31], [35], [63], [72], [80], [111], [129], [132], [146], involved in this connectivity category, with a heterogeneous set of task types (please refer to Fig. 2 for more details).…”
Section: Resultsmentioning
confidence: 99%
“…Effective connectivity studies are beginning to illuminate understanding about casual brain network interactions in OCD. For example, using a reward learning task, Alves-Pinto et al, showed alterations in intrinsic connectivity and contextual modulation of fronto-striatal circuits, mainly from the ventromedial PFC (vmPFC) to the left and right orbitofrontal cortex (OFC) ( 145 ). In another study, Schlösser and colleagues used a Stroop color-word task to elicit aberrant effective connectivity pathways between OCD and HC in the fronto-cingulate system, consistent with an over-active error control system during decision-making observed in OCD ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of the limbic system has been implicated in a number of models of OCD pathogenesis, including increased classical conditioning of compulsions; reduced modulation of a frontal-based habit system by hippocampal-based memory; and a deficit of implicit learning with compensation by explicit learning ( 22 24 ). Indeed, patients with OCD show reduced task-based reward learning, correlated with reduced activity in, and connectivity between, limbic structures such as the NAcc, ventral putamen, vmPFC, OFC, hippocampus, and amygdala ( 15 , 24 27 ). During episodes of increased symptomatology there is hyperactivation in limbic structures ( 28 , 29 ).…”
Section: Limbic Networkmentioning
confidence: 99%